2017
DOI: 10.1080/14737167.2017.1313118
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect cost of managing alzheimer’s disease and related dementias in the United States

Abstract: Introduction Care of individuals with Alzheimer’s Disease and Related Dementias (ADRD) poses special challenges. As the disease progresses, individuals with ADRD require increasing levels of medical care, caregiver support, and long-term care which can lead to substantial economic burden. Areas covered In this expert review, we synthesized findings from studies of costs of ADRD in the United States that were published between January 2006 and February 2017, highlighted major sources of variation in costs, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 54 publications
3
117
0
3
Order By: Relevance
“…Seventy percent of the lifetime cost of care is borne by family caregivers in the forms of unpaid caregiving and out‐of‐pocket expenses for items ranging from medications to food for the person with dementia 312,313 . Current estimates of the lifetime costs of care may underestimate the impact of a relative's dementia on family caregivers’ health and workplace productivity 314 …”
Section: Caregivingmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy percent of the lifetime cost of care is borne by family caregivers in the forms of unpaid caregiving and out‐of‐pocket expenses for items ranging from medications to food for the person with dementia 312,313 . Current estimates of the lifetime costs of care may underestimate the impact of a relative's dementia on family caregivers’ health and workplace productivity 314 …”
Section: Caregivingmentioning
confidence: 99%
“…312,313 Current estimates of the lifetime costs of care may underestimate the impact of a relative's dementia on family caregivers' health and workplace productivity. 314 Three of the main reasons caregivers provide care and assistance to a person with Alzheimer's or another dementia are (1) the desire to keep a family member or friend at home (65%), (2) proximity to the person with dementia (48%) and (3) the caregiver's perceived obligation to the person with dementia (38%). A13 Caregivers often indicate love and a sense of duty and obligation when describing what motivates them to assume care responsibilities for a relative or friend living with dementia.…”
Section: Unpaid Caregiversmentioning
confidence: 99%
“…Alzheimer's disease (AD) and stroke are severe cerebral pathologies with a very high socioeconomic impact and burden for society. These pathologies can occur together, may even interact [1,2], and both contribute to dementia. Vascular factors predisposing to stroke and cerebrovascular disease have been associated with dementia and more specifically with the enhancement of amyloid-β (Aβ) deposition [3].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of all these home healthcare available, patients who stay home need some level of informal care by their family members which add to the indirect costs. Published studies reported that indirect costs of diseases were 27%-89% of the total cost of healthcare (American Diabetes, 2018; Dagenais, Caro, & Haldeman, 2008;Deb, Thornton, Sambamoorthi, & Innes, 2017) which means that indirect cost is a major component of total healthcare cost.…”
mentioning
confidence: 99%